2018
DOI: 10.1002/2017jb014959
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Evolution of an Oceanic Intraplate Volcano From Seismic Reflection Data: A New Model for La Réunion, Indian Ocean

Abstract: High‐resolution seismic reflection profiles gathered in 2006 on La Réunion submarine flanks and surrounding abyssal plain, enabled characterization of the seismostratigraphy architecture of the volcaniclastic apron. Four seismic units are defined beyond the edifice base: (1) a basal unit, interpreted as pelagic sediment predating La Réunion volcanism; (2) a second unit showing low‐ to medium‐amplitude reflections, related to La Réunion emergence including the submarine explosive phase; (3) a high‐amplitude sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…In this study, we revisited the Monte Amarelo volcanic flank-collapse of Fogo Island and found that the deposition of the debris avalanche material may have triggered subsequent failures of pre-existing seafloor sediments in (at least) two phases. This is similar to what has been observed in the Lesser Antilles (Le Friant et al 2015;Brunet et al 2016), at La Réunion (Lebas et al 2018), and at Ritter Island (Karstens et al 2019;Watt et al 2019). It is not yet clear whether these two phases of seafloor sediment failure were synchronous as a result of a single flank-collapse, or if they reflect multiple, distinct events.…”
Section: Implications and Conclusionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, we revisited the Monte Amarelo volcanic flank-collapse of Fogo Island and found that the deposition of the debris avalanche material may have triggered subsequent failures of pre-existing seafloor sediments in (at least) two phases. This is similar to what has been observed in the Lesser Antilles (Le Friant et al 2015;Brunet et al 2016), at La Réunion (Lebas et al 2018), and at Ritter Island (Karstens et al 2019;Watt et al 2019). It is not yet clear whether these two phases of seafloor sediment failure were synchronous as a result of a single flank-collapse, or if they reflect multiple, distinct events.…”
Section: Implications and Conclusionsupporting
confidence: 76%
“…A similar two-fold nature of volcanic flank-collapse depositshummocky debris avalanche deposits accompanied by acoustically transparent to seismically chaotic deposits with a comparatively smooth upper surfacehas also been reported for flank-collapses at other locations, including in the Lesser Antilles (Watt et al, 2012a, b;Le Friant et al 2015;Brunet et al 2016); at La Réunion (Indian Ocean; Lebas et al 2018); and at Ritter Island (Papua New Guinea; Karstens et al 2019;Watt et al 2019). Drilled cores retrieved during IODP Expedition 340 in the Lesser Antilles indicated that widespread, seismically chaotic deposits (interpreted as equivalent to our MTD-B) primarily consist of hemipelagic mud interbedded with a combination of tephra, volcaniclastic layers, or bioclastic turbiditic deposits, which have undergone varying degrees of deformation (Le Friant et al 2015;Brunet et al 2016).…”
Section: The Two-fold Nature Of Fogo's Monte Amarelo Flank-collapsesupporting
confidence: 63%
“…Gravitational instabilities could occur on steep submarine slopes offshore Mayotte but also on the new submarine volcano 50 km offshore Petite Terre: such instabilities are not new on volcano edifices [e.g. Lebas et al, 2018, Le Friant et al, 2015, 2019, Lipman et al, 1988, Moore et al, 1989, Sassa et al, 2016, Watt et al, 2014. For instance, the collapse of the Anak Krakatau volcano in Indonesia in 2018 [93 Mm 3 , Gouhier and Paris, 2019] triggered a tsunami that hit the coast of the Sunda Strait with waves of up to 80 m [Grilli et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The subaerial and submarine morphology of volcanic islands results from the interplay between volcanic, tectonic, erosive and depositional processes acting at different time-scales Casalbore et al, 2015;Lebas et al, 2018;Quartau et al, 2018a). These processes and their influence on the geomorphology are very well known for the subaerial portions of volcanic islands (e.g., Thouret, 1999).…”
Section: Introductionmentioning
confidence: 99%